Analisis Pengelolaan Badan Usaha Milik Desa (Bumdes) Amanah Jati di Desa Jambu Timur - Nofi Haryanti; Subadriyah Subadriyah (Accounting Study Program, Faculty of Economics and Business, 2019)
This type of research is qualitative with a descriptive approach. The research aims to find out how the management of BUMDes Amanah Jati, how the conformity of Permendes No. 4 of 2015 in the organizational structure of BUMDes Amanah Jati, how the constraints in the formation of BUMDes Amanah Jati, as well as how the potential of BUMDes Amanah Jati to the Original Income of the Village (PADes) of Jambu Timur. The results of the study stated that the management of BUMDes Amanah Jati based on goals, goals, coordination up to the flow of management has described the management of BUMDes well, but there are still some factors that are not in accordance with the expectations in Permendes. The suitability of Permendes No. 4 of 2015 is not yet in accordance with the organizational structure and management so it will most likely be changed in accordance with government regulations. The obstacles faced in the most dominant management are HUMAN RESOURCES, in addition to facilities, infrastructure facilities and business premises. That's why BUMDes Amanah Jati until now has not been able to increase pades Jambu Timur.